2018
DOI: 10.17645/up.v3i1.1261
|View full text |Cite
|
Sign up to set email alerts
|

All Work and No Play? Facilitating Serious Games and Gamified Applications in Participatory Urban Planning and Governance

Abstract: As games and gamified applications gain prominence in the academic debate on participatory practices, it is worth examining whether the application of such tools in the daily planning practice could be beneficial. This study identifies a research-practice gap in the current state of participatory urban planning practices in three European cities. Planners and policymakers acknowledge the benefits of employing such tools to illustrate complex urban issues, evoke social learning, and make participation more acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 41 publications
0
86
0
Order By: Relevance
“…Government involvement is nonetheless essential by nature in this research stream and hence some researchers often simulated a governmental presence on the gamified tools they were evaluating [20,74,75,76]. Nonetheless, governmental presence in research is still observed [4,8,9,11,38,53,68,71]. In fact, although such reports are rare, some of the research has led to actual policy implementations [69].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Government involvement is nonetheless essential by nature in this research stream and hence some researchers often simulated a governmental presence on the gamified tools they were evaluating [20,74,75,76]. Nonetheless, governmental presence in research is still observed [4,8,9,11,38,53,68,71]. In fact, although such reports are rare, some of the research has led to actual policy implementations [69].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It is hence interesting to observe that a number of competitive implementations attempted to shift the focus of the competition from a competition between users to one between ideas [8,9,20,64,69], often employing leaderboards of ideas instead of or next to leaderboards of users. [2,7,8,9,16,28,31,41,55,64,73,76,78,79,80,81,83,86] 18 All [4,7,12,16,20,22,24,28,31,36,41,48,52,54,64,68,73,74,76,77,78,79,81,83] 24…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gamification is often applied in participatory urban planning by using game elements to enable citizens to debate or give feedback on specific plans and to propose ideas for small-scale projects (Ampatzidou, Gugerell, Constantinescu, Devisch, Jauschneg, & Berger, 2018). As a limitation of using gamification and serious games for citizens' engagement for urban planning, Ampatzidou et al (2018) stated that "the researches, planners and policy-makers do not make a clear distinction between games and gamified applications and use these terms interchangeably, which leads to a certain fuzziness in the practices they adopt and which often results in either disappointment, or the exclusion of such tools from the participatory process".…”
Section: Gamificationmentioning
confidence: 99%